ASSESSMENT OF IMPACT OF THE SOLAR I OIL SPILL ON THE INFAUNAL ASSEMBLAGES OF SOUTHERN GUIMARAS, PHILIPPINES - del Norte Campos, Annabelle G.C.; Narida-Nacionales, Erma (Marine Research in Indonesia, 2008)
The study was conducted between September and October 2006 in various sites both inside and outside the Taklong Island National Marine Reserve (TINMAR), southern Guimaras, Philippines, to immediately conduct a rapid 3-month assessment of the impact of the Solar I oil spill incident which occurred in August 11, 2006 in southern Guimaras. The assessment was made possible by the availability of baseline (pre-spill) data which were compared with the present data (post-spill). Results showed the drastic decrease in overall mean densities (no. m-2) and species richness in the infaunal assemblages within TINMAR in September 2006, or 1 month after the oil spill. In October 2006 however, a slight increase in both of these parameters was observed, albeit not significant. The decrease is taken as a disturbance, directly resulting from the oil spill. On the other hand, it is not clear at this time if the increase is the start of recovery in the infauna. Our results indicate the need for a continuous monitoring, to allow more definitive conclusions on a) whether the assemblages are recovering, and if indeed they are, b) how long this recovery will take place. Â